REKONSTRUKSI LEMBAR KERJA PADA PRAKTIKUM RESPIRASI TUMBUHAN DI KELAS 8 DAN ANALISISNYA BERDASARKAN DIAGRAM VEE - Sari, Abhelia Permata; Supriatno, Bambang; Amprasto, Amprasto (BIOEDUKASI (Jurnal Pendidikan Biologi), 2025)
Natural Science learning at the elementary, high school and university levels is certainly closely related to the practicum learning method. Practical activities, experiments and observations of objects and direct phenomena can motivate students and can bridge students to gain direct experience in studying science phenomena that cannot be obtained from ordinary textbooks. In preparing laboratory activities, it is necessary to consider whether the practicum worksheet can guide and direct students to form knowledge or not. Most practicum worksheets in circulation today have not yet reached the expected criteria, one of which is a worksheet on plant respiration in one of the science packagebooks for junior high school / MTs grade 8. Based on this, it is necessary to conduct an analysis and reconstruction to improve the existing worksheets. The method used in this research is descriptive qualitative method. There are three stages carried out in this study, namely: 1) analyzing the initial practicum worksheet; 2) conducting a limited trial on the initial practicum worksheet; and 3) reconstructing the practicum worksheet based on the trial results. Several weaknesses and obstacles were found during the trial which became the basis for improving the worksheets. Reconstruction of the worksheet was then carried out based on the suggestions for improvement obtained during the trial. After reconstruction, the practicum worksheet for respiration in plants experienced an increase in score, which was originally in the sufficient category (44%) to the very good category (83%).